Liver diseases at new coronavirus infection in pregnant women of Samara region - M. A. Kachkovskii; O. V. Kosheleva; G. M. Mingulova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The new coronavirus infection (COVID-19) is a life-threatening condition. The features of the treatment of COVID-19 in pregnant women are not sufficiently studied and contradictory, therefore, research in this area is relevant.Objective. Assess the presence of liver disease in pregnant women with COVID-19 infection during pregnancy and after childbirth, taking into account the treatment.Methods. A retrospective analysis of medical records of 43 pregnant women aged 19 to 39 years (mean age 29.1 ± 5.4 years) who were hospitalized with laboratory-confirmed COVID-19 infection was performed. The selection was carried out by the method of continuous sampling.Results. 17 women (39.5%) had an acute respiratory viral disease, 26 people (60.5%) were diagnosed with bilateral polysegmental pneumonia with pulmonary tissue damage from 5 to 25%. In the structure of extragenital pathology, 46.5% of women had anemia and 23.3% of diseases of the hepatobiliary system, including chronic non-calculous cholecystitis (4.7%), biliary dysfunction (7%), chronic viral hepatitis B (2.3%) and chronic viral hepatitis C (9.3%). 6.9% were diagnosed with cholestatic hepatosis of pregnant women before admission to the hospital. An increase in the level of transaminases above the upper normal values was noted in 69.8% of cases, alkaline phosphatase – in 76.7%. In the structure of pregnancy complications in women with COVID-19 infection, fetal hypoxia prevailed in 15 women (34.9%). In second place is premature rupture of amniotic fluid (16.3%) and fetal malnutrition (16.3%).Conclusions. Pregnant women with diseases of the hepatobiliary system and anemia are most susceptible to new coronavirus infection. They have an increase in the level of transaminases and alkaline phosphatase, which can be caused by liver damage due to the increased tropism of the virus to cholangiocytes and hepatocytes, as well as hepatotoxic drugs. The most common complications of pregnancy in women with a new infection are premature birth, fetal hypoxia, and antenatal death.